PENGELOLAAN KAS YANG EFISIEN DAN EFEKTIF DI PT. SURYA MEGA MUSTIKA - Lukman Surjadi; Agustina Wijaya; Agnes Ashianti (PROSIDING SERINA, 2021)
Cash is a current asset owned by the company which is used to finance the company's operational activities. Good cash management needs to be carried out by company management to maintain liquidity and the amount of cash owned by the company. To achieve this goal the company can prepare a cash budget. Based on the results of situational analysis and surveys, PT Surya Mega Mustika which is engaged in printing has not implemented efficient and effective cash management so that the extension team provides understanding through this PKM activity. PKM activities are carried out online in November 2021 via Zoom with employees of PT Surya Mega Mustika. The output target of this PKM is the publication of mandatory and additional articles.